Langmuir–Blodgett technique versatility for electrode modification and its ECL application - Snizhko, D.; Zholudov, Yu.; Kukoba, A.; Xu, G. (ISBC 2018, 2018)
In the work 9,10-diphenyl anthracene and rubrene were used to decorate an amphiphilic polymer matrix polymethylmethacrylate (PMMA) lm. ITO electrodes equipped with LB lm were used in ECL experiment with tripropylamine co-reactant. Obtained ECL response satis es expectation in looking for a new technology for ECL sensor fabrication.
Keywords: Langmuir{Blodgett technique; electrode modification; film